Physiological and biochemical characterization of trypsin from Neocaridina denticulata sinensis and its roles in ontogenesis and immune response - Dandan Feng; Yakun Song; Zuqi Wu; Wuruo Liu; Yuting Pu; Yangcan Gao; Yuying Sun; Jiquan Zhang (PLoS ONE, 2026)
Trypsin, a canonical serine protease in crustaceans, plays a crucial role in ontogeny and antibacterial defense. Whether these biological functions correlate with its catalytic characteristics remains unresolved in the freshwater shrimp Neocaridina denticulata sinensis . To address this gap, we characterized a trypsin gene from N. denticulata sinensis ( NdTryp ) and assessed both its biological roles and its prospective utility. NdTryp was predominantly expressed in the hepatopancreas, where it localized to storage cells (R-cells) and tubule-lining epithelial cells (ECTs). Across development, NdTryp transcripts were essentially absent during early embryogenesis but rose sharply at late stages, temporally coincident with hatching and the onset of feeding. After a challenge with Vibrio parahaemolyticus , the expression of NdTryp was induced, with the expression level significantly increased relative to the baseline expression level. RNA interference-mediated knockdown rendered shrimp more susceptible to infection and was accompanied by extensive hepatopancreatic injury, including epithelial detachment and disruption of the basement membrane. Biochemically, recombinant NdTryp (rNdTryp) displayed proteolytic activity over a broad temperature and pH span. Activity was differentially tuned by metal ions, with several divalent cations producing marked enhancement, whereas ferric iron exerted strong inhibition. Overall, our results showed that NdTryp functions as a multifunctional protease involved in both late embryonic development and innate antimicrobial defense. Furthermore, the robust stability of rNdTryp underscores its potential as an aquafeed additive and candidate for enzymatic biotransformation.